Transverse momentum and process dependent azimuthal anisotropies in √sNN = 8.16 TeV p+Pb collisions with the ATLAS detector - Alonso, Francisco (2020)
The azimuthal anisotropy of charged particles produced in √sNN = 8.16 TeV p+Pb collisions is measured with the ATLAS detector at the LHC. The data correspond to an integrated luminosity of 165 nb⁻¹ that was collected in 2016. Azimuthal anisotropy coefficients, elliptic v₂ and triangular v₃, extracted using two-particle correlations with a non-flow template fit procedure, are presented as a function of particle transverse momentum (pT) between 0.5 and 50 GeV. The v₂ results are also reported as a function of centrality in three different particle pT intervals. The results are reported from minimum-bias events and jet-triggered events, where two jet pT thresholds are used. The anisotropies for particles with pT less than about 2 GeV are consistent with hydrodynamic flow expectations, while the significant non-zero anisotropies for pT in the range 9–50 GeV are not explained within current theoretical frameworks. In the pT range 2–9 GeV, the anisotropies are larger in minimum-bias than in jet-triggered events. Possible origins of these effects, such as the changing admixture of particles from hard scattering and the underlying event, are discussed.